2016
DOI: 10.1002/casp.2272
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Well‐being of Homeless Individuals by Building Group Memberships

Abstract: There is growing recognition that social isolation and a lack of connectedness with social groups is one of the reasons why the subjective well-being of homeless individuals is generally worse than the rest of the population. Past research amongst a range of populations suggests that the ability of an individual to take on new group memberships and/or their ability to maintain their memberships in meaningful groups is an important predictor of well-being. In a mixed method study (N = 119), we examined the exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 41 publications
2
27
0
Order By: Relevance
“…In particular, service characteristics may contribute to whether the service staff and service users are seen as a positive identity or whether they represent a group to dissociate from (e.g. see Johnstone et al, 2016). These findings are consistent with previous research that examined the intersection between geography and homeless service provision.…”
Section: Service Characteristicssupporting
confidence: 87%
See 4 more Smart Citations
“…In particular, service characteristics may contribute to whether the service staff and service users are seen as a positive identity or whether they represent a group to dissociate from (e.g. see Johnstone et al, 2016). These findings are consistent with previous research that examined the intersection between geography and homeless service provision.…”
Section: Service Characteristicssupporting
confidence: 87%
“…Previous research has demonstrated that higher identification was associated with increased feelings of shared experiences, emotional support and understanding, and decreased social isolation and social isolation schemas Dingle et al, 2013;Johnstone et al, 2016). Subsequently, higher identification was associated with increased social interaction and social connectedness in general and this was theorised to form a scaffolding that facilitates the joining of new groups Dingle et al, 2013;Johnstone et al, 2016).…”
Section: Importance Of Identificationmentioning
confidence: 98%
See 3 more Smart Citations